Pembinaan dan Pengembangan Seni Masyarakat Desa Kaliurang Kecamatan Srumbung Kabupaten Magelang Jawa Tengah - Farid Azzani Prasanaya (Abdi Seni, 2022)
The mentorship and development of art potential in Kaliurang Village Community, Srumbung District, Magelang Regency, Central Java is one of the community service programs that aims to develop the art activities in the area. The performing arts in Kaliurang Village include Langen Taya, Karawitan Aji Budaya, Wayang Wong, and Dance. This community service program is also an initial step supported by the Kaliurang Village government as an effort to reactivate the arts in the area which is currently taking a break due to the Covid-19 pandemic. The purpose of this service is to overcome problems in every art in the field, one of which is the lack of knowledge and basic art skills possessed by art performers in the area. The learning method in this activity uses discussion, lecture, and experimental methods. The output of this community service activity is the performances of each art group.